Handbook of mathematical fluid dynamics. - Friedlander, Susan, 1946-; Serre, D. (Denis) (Elsevier, 2007)
This is the fourth volume in a series of survey articles covering many aspects of mathematical fluid dynamics, a vital source of open mathematical problems and exciting physics.